Pengaruh Modifikasi Penampang pada I-Girder dan Box Girder Beton Prategang terhadap Kekakuan dan Lendutan - Prayuda, Hakas (Department of Civil Engineering, Diponegoro University, 2021)
Prestressed concrete has been widely used in structural buildings, especially for big span length purposes. The prestressed concrete dimension cross sections normally are fixed, provided by the factory based on their experience for every span length. However, this size aspect can be developed to make better improvement. In this study, I and box girder shapes were modified with the same total cross-sectional area. Three types of modification have been made for each girder shape by giving the space on the middle for I girder and changing form from trapezoidal to rectangular section for box girder. The number of steel tendons for this research was made typically and same so that the stress and displacement can be compared fairly. Manual calculation was performed for all samples and was completed under three circumstances namely initial condition, loading condition, and final condition. Also, the manual calculation is according to Indonesian provisions, which are SNI 2833-2016 for the earthquake load and SNI 1725-2016 for normal loading on bridges. From the result, it is known that one shape for each girder shape has met the criteria for the smallest stress and displacement.